Railway track preservative as well as preparation method and application thereof

By preparing phosphonate crystalline nanomaterials and other components as corrosion inhibitors, a high-strength anti-corrosion coating is formed, solving the problem of rapid corrosion of railway tracks in specific areas and achieving long-term protection and a low-cost anti-corrosion solution.

CN119264788APending Publication Date: 2025-01-07JIANGSU TEHAO NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411541953.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Railway tracks corrode rapidly in coastal, riverside, mountainous, and tunnel areas. Existing protection technologies cannot effectively extend their service life, leading to frequent replacements, wasting resources, and affecting traffic safety.

Method used

A corrosion inhibitor composed of phosphonate crystalline nanomaterials and other components is used to prepare nanoparticles through a chelation reaction, forming a high-strength and stable anti-corrosion coating. The coating is cured at high temperature and interpenetrates with the substrate, improving adhesion and anti-corrosion performance.

Benefits of technology

It provides long-lasting protection, is easy to use, has strong adhesion, is inexpensive, and can effectively prevent railway track corrosion and extend service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264788A_ABST
    Figure CN119264788A_ABST
Patent Text Reader

Abstract

The invention discloses a railway track preservative as well as a preparation method and application thereof. The preservative comprises the following components in percentage by mass: 1%-3% of silicon dioxide sol particles, 0.5%-3% of metal nano sol particles, 10%-20% of a phosphonate crystal form nano material, 1%-5% of epoxy acrylic resin, 1%-5% of silicon resin and the balance of water. The phosphonate crystal form nano material is prepared by inducing polyhydric alcohol phosphate and zinc oxide to be subjected to chelation reaction through sodium fluoroaluminate. The mass ratio of the sodium fluoroaluminate to the polyhydric alcohol phosphate to the zinc oxide is (0.02 to 0.05) to (5 to 10) to (0.5 to 1). The anti-corrosion agent provided by the invention has ultra-long-time protection performance, also has the characteristics of being convenient to implement, strong in field random operability, strong in adhesive force (avoiding the anti-corrosion coating from falling off due to high-frequency resonance during high-speed running of a train) and low in cost, and can solve the problem of corrosion protection of a railway track.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of antiseptics, and in particular to a railway track antiseptic and a preparation method and application thereof. Background Art

[0002] In recent years, my country's high-speed railway network has expanded rapidly, but common railway tracks are exposed in the wild, and wind and rain in the wild will accelerate the corrosion of the tracks, especially in coastal, riverside, and mountain tunnel areas. The corrosion rate of the tracks is even faster. Once corroded to a certain extent, the tracks will lose their physical and mechanical properties, affecting driving safety. Therefore, the safety and durability of railway track projects are currently facing unprecedented challenges.

[0003] According to national standards and regulations of the railway department, the replacement cycle of rails is 15 years or when the mileage exceeds 6 million tons. However, due to the vast territory of China and the different railway use environments in different regions, the actual service life varies greatly. The rails used on the main trunk lines need to be fully replaced every ten years according to the overhaul cycle, while the overhaul cycle on the secondary trunk lines is about 10 to 15 years. However, in coastal, riverside and mountainous tunnel areas, the corrosion rate of the tracks is serious, which greatly shortens the service life of the engineering structure. At present, railway maintenance personnel need to regularly inspect, detect damage and repair and maintain the tracks in such areas every week. Even so, the railway tracks in high-corrosion areas are facing the situation of needing to be completely replaced every 2-3 years, wasting a lot of material and financial resources. Therefore, the development of track metal protection technology and the innovation of solutions are crucial to the national rail transit strategy. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a railway track preservative and its preparation method and application. The provided preservative meets the requirements of real-time implementation off-site and has the characteristics of simple operation, strong corrosion resistance and long service life.

[0005] The above object of the present invention is achieved through the following technical solutions:

[0006] The first aspect of the present invention provides a method for preparing a phosphonate crystalline nanomaterial, comprising the following steps: sodium fluoroaluminate induces a chelating reaction between polyol phosphate ester (PAPE) and zinc oxide to obtain the phosphonate crystalline nanomaterial; the mass ratio of the sodium fluoroaluminate, polyol phosphate ester and zinc oxide is (0.02-0.05):(5-10):(0.5-1).

[0007] The above reaction mainly produces (PAPE-ZnO) nNanoparticles aggregated when (3000 < n < 20000). Different from ordinary chelation products, these nanoparticles are precipitated-type crystalline nanoparticles with high strength formed by chelation under ultra-strong acidic conditions and atomic coordination in PAPE. They have a high-strength crystal structure, high stability, and high hardness, which play a decisive role in the performance of the final anti-corrosion coating and are also the main components of the preservative.

[0008] Sodium hexafluoroaluminate plays a key role as a seed crystal in this synthesis, inducing the formation of the initial crystal structure and promoting the aggregation of PAPE, zinc ions, and dissolved zinc oxide around it to form crystalline nanoparticles.

[0009] Furthermore, the reaction time is 24 - 72 h.

[0010] Furthermore, after the reaction, the steps of filtration, washing, and drying are also included.

[0011] In a specific embodiment, the preparation method includes the following steps: adding polyol phosphate, zinc oxide, and sodium hexafluoroaluminate to water, and obtaining the phosphonate crystalline nanomaterial after the reaction.

[0012] In a specific embodiment, the phosphonate crystalline nanomaterial is synthesized from the following components by mass percentage: polyol phosphate 5% - 10%, zinc oxide 0.5% - 1%, sodium hexafluoroaluminate 0.02% - 0.05%, and the balance is water.

[0013] The second aspect of the present invention provides a phosphonate crystalline nanomaterial prepared by the method described in the first aspect.

[0014] The third aspect of the present invention provides a preservative, which includes the following components by mass percentage: silica sol particles 1% - 3%, metal nanosol particles 0.5% - 3%, phosphonate crystalline nanomaterial 10% - 20%, epoxy acrylate resin 1% - 5%, silicone resin 1% - 5%, and the balance is water;

[0015] The phosphonate crystalline nanomaterial is prepared by inducing the chelation reaction of polyol phosphate and zinc oxide with sodium hexafluoroaluminate; the mass ratio of sodium hexafluoroaluminate, polyol phosphate, and zinc oxide is (0.02 - 0.05):(5 - 10):(0.5 - 1).

[0016] Furthermore, the content of sodium ions in the silica sol particles is less than 5 ppm.

[0017] The silica sol particles used in the present invention are of low-sodium type because sodium ions, as alkaline metals, will increase the conductivity of the coating in the anti-corrosion coating, thereby increasing the possibility of local galvanic corrosion and ultimately affecting the corrosion protection service life of the anti-corrosion coating.

[0018] The silica sol particles currently on the market have the problem of poor alkali resistance. If the railway track is corroded, the local pH value will increase significantly, even exceeding 12, forming a high alkalinity environment. Once the nanomaterial is not alkali-resistant, local corrosion will occur, causing the anti-corrosion coating to fall off, thereby affecting the overall performance of the product. Therefore, the silica sol particles provided by the present invention are alkali-resistant, and the alkali resistance is 5wt% sodium hydroxide solution and above.

[0019] Furthermore, the metal nano-sol particles are selected from one or more of aluminum oxide sol particles, cerium oxide sol particles and magnesium oxide sol particles.

[0020] Furthermore, the particle size of the metal nano-sol particles is not greater than 30 nanometers, preferably 5 to 30 nanometers.

[0021] The metal nano-sol particles used in the present invention are used as the core material, and their properties will ultimately affect the rubbing properties of the nano-particles in the anti-corrosion coating, thereby affecting the overall anti-corrosion performance of the coating. The metal nano-sol particles selected in the present invention have the effect of cathodic protection and are an important raw material in cathodic protection. After local corrosion occurs, the alumina sol can form aluminum hydroxide in an alkaline environment to fill the corrosion sites and inhibit further corrosion. Cerium oxide nano-sol is an environmentally friendly passivation material in industrial applications. The cerium ion is in a +4 valent metal ion state, which can produce passivation characteristics for active metals and significantly help improve the protective performance of the coating medium.

[0022] The epoxy acrylic resin used in the present invention contains epoxy groups and acrylic functional groups. The epoxy groups can improve the adhesion between the resin molecules and the nano sol particles (silicon dioxide sol particles and metal nano sol particles) and the metal substrate, while the acrylic groups can improve the ultraviolet light aging resistance and weather resistance of the anti-corrosion coating, thereby increasing the service life of the final anti-corrosion coating.

[0023] The silicone resin used in the present invention can play a good synergistic role with the epoxy acrylic resin in terms of dispersion and sealing. At the same time, the anticorrosive agent provided by the present invention needs to be heated at a relatively high temperature to form an anticorrosive coating during the on-site implementation of the track, which promotes the interpenetration of the nano-sol particles and the metal substrate, while the adhesion of the epoxy acrylic resin will be slightly reduced under high temperature conditions, so the addition of a high temperature resistant organic silicone resin can compensate for the impact of the implementation process.

[0024] Furthermore, the particle size of the zinc oxide is 2000-2500 mesh.

[0025] The fourth aspect of the present invention provides a method for preparing the preservative described in the third aspect, comprising the following steps: adding silica sol particles, metal nano sol particles, phosphonate crystal nanomaterials, epoxy acrylic resin and silicone resin into water, and mixing to obtain the preservative.

[0026] The fifth aspect of the present invention provides the use of the phosphonate crystalline nanomaterial described in the first aspect and the preservative described in the third aspect in railway track engineering.

[0027] Beneficial effects of the present invention:

[0028] The anticorrosive provided by the present invention has ultra-long-term protective performance, is easy to implement, has strong random operability in the field, has strong adhesion (to avoid the high-frequency resonance of high-speed trains causing the anti-corrosion coating to fall off), and is low in cost, and can solve the corrosion protection problem of railway tracks. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the full XPS spectrum of the phosphonate crystalline nanomaterial in Example 1.

[0030] Figure 2 This is the Zn 2p high-resolution XPS spectrum of the phosphonate crystalline nanomaterial in Example 1.

[0031] Figure 3 This is the P 2p high-resolution XPS spectrum of the phosphonate crystalline nanomaterial in Example 1.

[0032] Figure 4 The figure is a photo of an anti-corrosion coating formed after the anti-corrosion agent of the present invention is applied to a railway track. DETAILED DESCRIPTION

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0034] The invention provides a preservative, which comprises the following components in percentage by mass: 1%-3% of silicon dioxide sol particles, 0.5%-3% of metal nano sol particles, 10%-20% of phosphonate crystal nano material, 1%-5% of epoxy acrylic resin, 1%-5% of silicone resin, and the balance is water.

[0035] In a specific embodiment, the silica sol particles are selected from one or more of low sodium type JN-20, low sodium type JN-25, low sodium type JN-30, alkali-resistant type HJA-20, alkali-resistant type HJA-30-M-25, alkali-resistant type HJA-20B, and alkali-resistant type HJA-20C.

[0036] In a specific embodiment, there are many manufacturers of silica sol particles, but there are huge differences in synthesis methods, sizes, polymerization degrees, hydroxyl groups, synthesis conditions, etc., which have a huge impact on the performance of the final product. The silica sol particles provided by the present invention are purchased from Shandong Yinfeng Nanomaterial Co., Ltd.

[0037] In a specific embodiment, the activity and crystal structure of the metal nano sol particles prepared by different synthesis processes are significantly different. The alumina sol particles provided by the present invention are purchased from Shanghai Wenjing Chemical Co., Ltd. GM-43 type and GM-40 type, the cerium oxide sol particles are purchased from Wuhu Xinda New Materials Co., Ltd. super soluble CeO2, and the magnesium oxide sol particles are purchased from Shanghai Naio Nano Technology Co., Ltd. 40-type.

[0038] In a specific embodiment, the spatial structure and degree of polymerization of the epoxy acrylic resin will also have a huge impact on the performance of the product. The epoxy acrylic resin provided by the present invention is selected from one or more of GS-5200, GS-5200B and GS-5200C of Jiangsu Guangshu Chemical Technology Co., Ltd., which not only has good adhesion and aging resistance, but also has a good dispersion and suspension effect on nano sol particles (silicon dioxide sol particles and metal nano sol particles), thereby improving product stability.

[0039] In a specific embodiment, the silicone resin provided by the present invention is a general-purpose high temperature resistant silicone resin purchased from Wuhan Science and Technology Co., Ltd.

[0040] The preparation method of the preservative provided by the invention comprises the following steps: adding silicon dioxide sol particles, metal nano sol particles, phosphonate crystal nano materials, epoxy acrylic resin and silicone resin into water, and mixing to obtain the preservative.

[0041] In a specific embodiment, the preparation method of the preservative comprises the following steps:

[0042] S1. Add water to the stirred tank and start stirring at a rate of 30-40 r / min;

[0043] S2, add silica sol particles and stir for 1-2 hours to make them evenly dispersed;

[0044] S3, adding metal nano-sol particles and stirring for 2-3 hours to make them evenly dispersed;

[0045] S4, adding phosphonate crystalline nanomaterials, and increasing the stirring rate to 60-70r / min to make them evenly dispersed;

[0046] S5. Add epoxy acrylic resin and stir for 5-6 hours to make it dissolve evenly;

[0047] S6. Slowly add silicone resin and stir for 2-3 hours to make it dissolve evenly;

[0048] S7. Make up the remaining water and continue stirring for 10-12 hours to obtain the preservative.

[0049] In a specific embodiment, the phosphonate crystalline nanomaterial is prepared by sodium fluoroaluminate inducing a chelating reaction between polyol phosphate and zinc oxide, and is synthesized from the following components in percentage by mass: 5%-10% polyol phosphate, 0.5%-1% zinc oxide, 0.02%-0.05% sodium fluoroaluminate, and the remainder is water.

[0050] In a specific embodiment, different processes for synthesizing polyol phosphates use different base alcohol types and phospholipid modification degrees, and their performances differ greatly. The polyol phosphates provided by the present invention are purchased from Shandong Xintai Water Treatment Technology Co., Ltd.

[0051] In a specific embodiment, the preparation method of the phosphonate crystalline nanomaterial comprises the following steps: adding polyol phosphate, zinc oxide and sodium fluoroaluminate into water, and obtaining the phosphonate crystalline nanomaterial after reaction.

[0052] In a specific embodiment, the preparation method of the phosphonate crystalline nanomaterial comprises the following steps:

[0053] (1) Add an appropriate amount of water to the reactor and start stirring at a rate of 30-40 r / min;

[0054] (2) Add polyol phosphate and stir for 20-30 minutes to achieve uniform dissolution;

[0055] (3) Slowly add zinc oxide and react for 2-3 hours;

[0056] (4) Sodium fluoroaluminate is added, and nanocrystals will gradually precipitate after 20-24 hours. After 70-72 hours, the precipitated crystals are filtered and washed 3-5 times;

[0057] (6) Drying the filtered and washed nanocrystalline particles using a vacuum freeze dryer to obtain the phosphonate crystalline nanomaterial.

[0058] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0059] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0060] Example 1

[0061] A preservative comprises the following components in percentage by mass: 1.5% of low-sodium JN-20 silica sol particles, 1% of GM-40 alumina sol particles, 15% of phosphonate crystal nanomaterials, 1% of GS-5200B epoxy acrylic resin, 2% of general-purpose high-temperature resistant silicone resin, and the balance is water.

[0062] The preparation method of the preservative of Example 1 comprises the following steps:

[0063] S1. Add water into the stirred tank and start stirring at a stirring rate of 30 r / min;

[0064] S2, add low sodium JN-20 silica sol particles and stir for 1 hour to make them evenly dispersed;

[0065] S3, add GM-40 alumina sol particles and stir for 2 hours to make them evenly dispersed;

[0066] S4, adding phosphonate crystalline nanomaterials, and increasing the stirring rate to 60r / min to make them dispersed evenly;

[0067] S5, add GS-5200B epoxy acrylic resin and stir for 5 hours to make it dissolve evenly;

[0068] S6. Slowly add the general-purpose high-temperature resistant silicone resin and stir for 2 hours to make it dissolve evenly;

[0069] S7. Make up the remaining water and continue stirring for 10 hours to obtain the preservative.

[0070] In Example 1, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 5% hexavalent alcohol phosphate, 0.5% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method comprises the following steps:

[0071] (1) Add appropriate amount of water to the reactor and start stirring at a stirring rate of 35 r / min;

[0072] (2) adding hexavalent alcohol phosphate and stirring for 20 minutes to achieve uniform dissolution;

[0073] (3) Slowly add zinc oxide and react for 2 hours;

[0074] (4) Sodium fluoroaluminate is added, and nanocrystals will gradually precipitate after 24 hours. After 72 hours, the precipitated crystals are filtered and washed 3-5 times;

[0075] (6) Drying the filtered and washed nanocrystalline particles using a vacuum freeze dryer to obtain the phosphonate crystalline nanomaterial.

[0076] The phosphonate crystalline nanomaterials in Example 1 were characterized by X-ray photoelectron spectroscopy (XPS). Figure 1 As shown, we can see obvious characteristic peaks of P and Zn elements; Figure 2 (Zn 2p high resolution XPS spectrum) and Figure 3 (P 2p high-resolution XPS spectrum) shows the existence of PO-Zn bonds in phosphonate crystalline nanomaterials.

[0077] Example 2

[0078] A preservative comprises the following components in percentage by mass: 3% of alkali-resistant HJA-20 silica sol particles, 0.5% of 40-type magnesium oxide sol particles, 10% of phosphonate crystal nanomaterials, 15% of GS-5200B epoxy acrylic resin, 3% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is substantially the same as that of Example 1.

[0079] In Example 2, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 10% hexavalent alcohol phosphate, 1% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method is basically the same as that in Example 1.

[0080] Example 3

[0081] A preservative comprises the following components in percentage by mass: 2% of alkali-resistant HJA-30-M-25 silica sol particles, 3% of GM-43 alumina sol particles, 20% of phosphonate crystal nanomaterials, 3% of GS-5200 epoxy acrylic resin, 1% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is substantially the same as that of Example 1.

[0082] In Example 3, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 5% hexavalent alcohol phosphate, 0.5% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method is basically the same as that in Example 1.

[0083] Example 4

[0084] A preservative comprises the following components in percentage by mass: 1% of low-sodium JN-25 silica sol particles, 0.5% of super-soluble CeO2 sol particles, 10% of phosphonate crystal nanomaterials, 1% of GS-5200C epoxy acrylic resin, 1% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is basically the same as that of Example 1.

[0085] In Example 4, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 7.5% hexavalent alcohol phosphate, 0.75% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method is basically the same as that in Example 1.

[0086] Example 5

[0087] A preservative comprises the following components in percentage by mass: 3% of low-sodium JN-30 silica sol particles, 3% of 40-type magnesium oxide sol particles, 20% of phosphonate crystal nanomaterials, 5% of GS-5200B epoxy acrylic resin, 5% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is substantially the same as that of Example 1.

[0088] In Example 5, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 5% hexavalent alcohol phosphate, 1% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method is basically the same as that in Example 1.

[0089] Example 6

[0090] A preservative comprises the following components in percentage by mass: 1% of low-sodium HJA-20C silica sol particles, 0.5% of 40-type magnesium oxide sol particles, 20% of phosphonate crystal nanomaterials, 5% of GS-5200 epoxy acrylic resin, 1% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is substantially the same as that of Example 1.

[0091] In Example 6, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 10% hexavalent alcohol phosphate, 0.5% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method is basically the same as that in Example 1.

[0092] Comparative Example 1

[0093] A preservative comprises the following components in percentage by mass: 1.5% of low-sodium JN-20 silica sol particles, 1% of GM-40 alumina sol particles, 1% of GS-5200B epoxy acrylic resin, 2% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is substantially the same as that of Example 1.

[0094] Comparative Example 2

[0095] A preservative comprises the following components in percentage by mass: 1% of low-sodium JN-20 silica sol particles, 0.5% of 40-type magnesium oxide sol particles, 15% of phosphonate crystal nanomaterials, 5% of GS-5200 epoxy acrylic resin, 1% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is substantially the same as that of Example 1.

[0096] In Comparative Example 2, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 15% hexavalent alcohol phosphate, 0.5% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method is basically the same as that in Example 1.

[0097] Comparative Example 3

[0098] A preservative comprises the following components in percentage by mass: 1% of low-sodium HJA-20C silica sol particles, 0.6% of 40-type magnesium oxide sol particles, 20% of phosphonate crystal nanomaterials, 5% of GS-5200 epoxy acrylic resin, 1% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is substantially the same as that of Example 1.

[0099] In Comparative Example 3, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 10% hexavalent alcohol phosphate, 1.5% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method is basically the same as that in Example 1.

[0100] Comparative Example 4

[0101] A preservative comprises the following components in percentage by mass: 1% of low-sodium HJA-20C silica sol particles, 0.5% of GM-40 alumina sol particles, 16% of phosphonate crystal nanomaterials, 5% of GS-5200 epoxy acrylic resin, 1% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is substantially the same as that of Example 1.

[0102] In Comparative Example 4, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 10% hexavalent alcohol phosphate, 0.1% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method is basically the same as that in Example 1.

[0103] Comparative Example 5

[0104] A preservative comprises the following components in percentage by mass: 1% of low-sodium HJA-20C silica sol particles, 0.5% of 40-type magnesium oxide sol particles, 20% of phosphonate crystal nanomaterials, 5% of GS-5200 epoxy acrylic resin, 1% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is substantially the same as that of Example 1.

[0105] In Comparative Example 5, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 2% hexavalent alcohol phosphate, 0.5% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method is basically the same as that in Example 1.

[0106] Comparative Example 6

[0107] A preservative comprises the following components in percentage by mass: 5% of alkali-resistant HJA-20 silica sol particles, 0.5% of 40-type magnesium oxide sol particles, 30% of phosphonate crystal nanomaterials, 0.5% of GS-5200B epoxy acrylic resin, 0.5% of general-purpose high-temperature resistant silicone resin, and the balance is water; the preparation method is substantially the same as that of Example 1.

[0108] In Example 2, the phosphonate crystalline nanomaterial is synthesized from the following components in percentage by mass: 10% hexavalent alcohol phosphate, 1% zinc oxide (2000 mesh), 0.02% sodium fluoroaluminate, and the balance is water; the preparation method is basically the same as that in Example 1.

[0109] Test Example 1

[0110] The antiseptics of Examples 1-6 and Comparative Examples 1-6 were used to coat the railway tracks, and the specific operations were as follows:

[0111] (1) Laser rust removal on the surface of railway tracks until a bright metal substrate is revealed;

[0112] (2) Applying a preservative to the surface of a railway track in one application;

[0113] (3) Using a movable infrared heater, the coating interface is heated at a heating rate of 5°C / min, heating is stopped when the temperature reaches 400°C, and the temperature is maintained at a constant temperature for 10 minutes;

[0114] (4) After cooling to 100°C, apply the preservative once again;

[0115] (5) Using a movable infrared heater, the coating interface is heated at a heating rate of 5°C / min, heating is stopped when the temperature reaches 400°C, and the temperature is maintained at a constant temperature for 10 min;

[0116] (6) After cooling to 100°C, apply the preservative once again;

[0117] (7) Using a movable infrared heater, the coating interface is heated at a heating rate of 5°C / min, heating is stopped when the temperature reaches 400°C, and the temperature is maintained at a constant temperature for 10 min;

[0118] (8) Stop heating and cool to room temperature to obtain an anti-corrosion coating on the surface of the railway track. Figure 4 shown.

[0119] The corrosion resistance test of the railway track coated with the anti-corrosion agent is carried out as follows:

[0120] (1) The railway track sample coated with the preservative was placed in an ultrasonic instrument (power 2 kW / h) containing pure water, and then taken out and dried after ultrasonication for 2 hours;

[0121] (2) According to the national standard GB2007-1991, the sample treated in step (1) is subjected to a salt spray test and taken out after 100 hours;

[0122] (3) Repeat steps (1) and (2) ten times and observe the surface corrosion.

[0123] The use of high-frequency vibration of an ultrasonic instrument is intended to simulate the scenario of a train passing through a railway track at high speed. During the simulation, the resonance damage to the interface layer between the anti-corrosion coating and the track substrate occurs. The salt spray test uses a 3.5% NaCl aqueous solution to simulate the seawater mist corrosion medium coating to accelerate corrosion. Industry experience data shows that a 100-hour salt spray test is equivalent to 1.5 years of natural environment corrosion, and a 10-cycle test simulates the state after 15 years of natural corrosion environment. If corrosion occurs after 10 cycles, it is judged as qualified, and if corrosion occurs within 10 cycles, it is judged as unqualified.

[0124] The test results are shown in Table 1:

[0125] Table 1

[0126] Test Results Example 1 Corrosion started to appear after 11 cycles Example 2 Corrosion started to appear after 12 cycles Example 3 Corrosion started to appear after 11 cycles Example 4 Corrosion started to appear after 14 cycles Example 5 Corrosion started to appear after 12 cycles Example 6 Corrosion started to appear after 13 cycles Comparative Example 1 Corrosion started to appear after 5 cycles Comparative Example 2 Corrosion started to appear after 8 cycles Comparative Example 3 Corrosion started to appear after 7 cycles Comparative Example 4 Corrosion started to appear after 9 cycles Comparative Example 5 Corrosion started to appear after 7 cycles Comparative Example 6 Corrosion started to appear after 6 cycles

[0127] The present invention adopts a recoating process to increase the coating thickness and ensure that the anti-corrosion service life of the dielectric coating can reach 15 years; the high-temperature heating used is used to solidify the resin in the preservative and promote its cross-linking, and on the other hand, to rub and rearrange the nano-sol particles (silicon dioxide sol particles and metal nano-sol particles) at high temperature to improve the density of the nano-particles, and also to promote the interpenetration of the metal nano-particles in the anti-corrosion coating and the iron elemental crystal in the substrate, thereby improving its adhesion and passivation properties.

[0128] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A preservative, characterized in that The invention comprises the following components in percentage by mass: 1%-3% of silica sol particles, 0.5%-3% of metal nano-sol particles, 10%-20% of phosphonate crystal nano-materials, 1%-5% of epoxy acrylic resin, 1%-5% of silicone resin, and the balance is water; The phosphonate crystalline nanomaterial is prepared by sodium fluoroaluminate inducing a chelating reaction between polyol phosphate and zinc oxide; the mass ratio of the sodium fluoroaluminate, polyol phosphate and zinc oxide is (0.02-0.05):(5-10):(0.5-1).

2. The preservative according to claim 1, characterized in that The content of sodium ions in the silica sol particles is less than 5 ppm.

3. The preservative according to claim 1, characterized in that The metal nano-sol particles are selected from one or more of aluminum oxide sol particles, cerium oxide sol particles and magnesium oxide sol particles.

4. The preservative according to claim 1, characterized in that The particle size of the metal nano-sol particles is no greater than 30 nanometers.

5. The preservative according to claim 1, characterized in that The particle size of the zinc oxide is 2000-2500 meshes.

6. A method for preparing the preservative according to any one of claims 1 to 5, characterized in that: The following steps are involved: The preservative is obtained by adding silica sol particles, metal nano sol particles, phosphonate crystal nano material, epoxy acrylic resin and silicone resin into water and mixing them.

7. A method for preparing a phosphonate crystalline nanomaterial, characterized in that: The following steps are involved: Sodium fluoroaluminate induces a chelating reaction between polyol phosphate and zinc oxide to obtain the phosphonate crystal nanomaterial; the mass ratio of the sodium fluoroaluminate, polyol phosphate and zinc oxide is (0.02-0.05):(5-10):(0.5-1).

8. The preparation method according to claim 7, characterized in that: The specific operation is: adding polyol phosphate, zinc oxide and sodium fluoroaluminate into water, and obtaining the phosphonate crystal nano material after reaction.

9. A phosphonate crystalline nanomaterial prepared by the method according to claim 7 or 8.

10. Use of the preservative according to any one of claims 1 to 5 and the phosphonate crystalline nanomaterial according to claim 9 in railway track engineering.